IPM Model for Management of Bemisia tabaci (Aleyrodidea: Hemiptera) on Tomato Crop: Management of Bemisia tabaci on Tomato Crop (Biological Sciences - PJSIR, 2022)
The whitefly (Bemisia tabaci) is a notable pest of vegetables and elaborate cash crops include tomato plant. The current study was carried out to develop an IPM model to control B. Tobacco on tomato crop. The following techniques have been utilized in controlling the population of whitefly, such as mechanical traps (yellow sticky card), biological control agent (Chrysoperla carnea), organic pesticide (Neem leaf extracts), integrated (Sticky card trap, C. Cornea, NLE) and un-treated. The adult population reduction % was recorded, (77.36%) in yellow sticky card trap, (63.97%) in C. Carnea, (85.20%) in NLE and in integrated plot (80.66%). In nymph population, (33.65%) in yellow sticky card trap, (82.15%)  in Carnea, (92.26%) in the NLE and in integrated plot (89.86%) reduction was recorded. Therefore, the use of NLE and yellow sticky card traps the proposed IMP strategy which are highly effective in protecting the tomato crops from the whitefly on a large scale.